De novo Assembly of the Pokeweed Genome Provides Insight Into Pokeweed Antiviral Protein (PAP) Gene Expression - Neller, Kira C. M.; Diaz, Camille A.; Platts, Adrian E.; Hudak, Katalin A. (Frontiers in Plant Science, 2019)
Ribosome-inactivating proteins are RNA glycosidases thought to function in defense against pathogens. These enzymes remove purine bases from RNAs, including rRNA; the latter activity decreases protein synthesis in vitro, which is hypothesized to limit pathogen proliferation by causing host cell death. Pokeweed antiviral protein (PAP) is a ribosome-inactivating protein synthesized by the American pokeweed plant (Phytolacca americana). PAP inhibits virus infection when expressed in crop plants, yet little is known about the function of PAP in pokeweed due to a lack of genomic tools for this non-model species. In this work, we de novo assembled the pokeweed genome and annotated protein-coding genes. Sequencing comprised paired-end reads from a short-insert library of 83X coverage, and our draft assembly (N50 = 42.5 Kb) accounted for 74% of the measured pokeweed genome size of 1.3 Gb. We obtained 29,773 genes, 73% of which contained known protein domains, and identified several PAP isoforms. Within the gene models of each PAP isoform, a long 5’ UTR intron was discovered, which was validated by RT-PCR and sequencing. Presence of the intron stimulated reporter gene expression in tobacco. To gain further understanding of PAP regulation, we complemented this genomic resource with expression profiles of pokeweed plants subjected to stress treatments (jasmonic acid, salicylic acid, polyethylene glycol, and wounding). Cluster analysis of the top differentially expressed genes indicated that some PAP isoforms shared expression patterns with genes involved in terpenoid biosynthesis, jasmonic acid-mediated signalling, and metabolism of amino acids and carbohydrates. The newly sequenced promoters of all PAP isoforms contained cis-regulatory elements associated with diverse biotic and abiotic stresses. These elements mediated response to jasmonic acid in tobacco, based on reporter constructs containing promoter truncations of PAP-I, the most abundant isoform. Taken together, this first genomic resource for the Phytolaccaceae plant family provides new insight into the regulation and function of PAP in pokeweed.